Synthesis, structure and properties of selected lithiated transition metal oxides - Davidson, Jean Isobel (My University, 1996)
This thesis discloses a newly discovered series of compounds, Li₂CryMn₂-yO₄, wherein 0.1≤y≤1.9. This series consists of two solid solutions regions with a cross-over occurring at a composition near y = 1.4. The chemical structure of these phases was identified by x-ray powder diffraction. Phases with y≥1.4 have an ordered rock salt structure in which the lithium and transition metal cations form alternating layers between the sheets of oxygen atoms. The phases with y<1.4 have a different rock salt related structure in which the lithium ions and transition metal ions are arranged in interleaving chains within the cubic-close-packed oxygen framework. The resulting structures are distorted from cubic symmetry by the presence of the Jahn-Teller ion, Mn³⁺. The compositions with y< 1.65 were found to be particularly useful as cathodes in lithium ion type, electrochemical cells. The chemical and ordered magnetic structure of three materials, orthorhombic LiMnO₂, 1T-Li₂NiO₂ and a low temperature form of LiFeO₂ were determined from neutron diffraction data. LT-LiFeO₂ and 1T-Li₂NiO₂ are metastable phases prepared by chimie douce synthetic methods. A detailed study of the magnetic properties of 1T-Li₂NiO₂ and orthorhombic LiMnO₂ revealed complex behaviour involving a competition between two- and three-dimensional ordering. Neutron diffraction was also employed to identify the chemical structure of Li₂NiMnO₄. The electrochemical behaviour of orthorhombic LiMnO₂, LT-LiFeO₂. Li₂NiMnO₄ and Li₂Ni₁.₅Mn₀.₅O₄ was investigated in lithium ion cells. Orthorhombic LiMnO₂ proved to be particularly useful as a cathode material as it undergoes a phase transition in situ to the lithiated spinel phase λ-Li₂Mn₂O₄. Consequently, orthorhombic LiMnO₂ provides a convenient, air stable precursor to the electrochemically useful, but not air stable, λ-Li₂Mn₂O₄ phase.
Keywords: Chemistry; Chemistry